L’Homme et les échanges Études des contacts passés (Ausonius Éditions, 2024)
From the Plio-Pleistocene to the present day, man has moved over ever larger territories, bringing with him his goods, his knowledge and his beliefs. He has complexified his social links and exploited his natural and cultural environment. Whatever the time or place, populations have sought contact, making exchanges an intrinsic feature of humanity. In order to explore these past interactions, it is important for archaeological sciences to establish suitable approaches for defining the context in which exchanges took place. This book takes a multi-disciplinary approach, highlighting the richness and diversity of these interactions and how they are perceived from an archaeological point of view. This panorama is not limited to the exchanges themselves, but also covers all the notions that accompany them: the nature of the motivations driving people to exchange, the spaces of exchange and their characteristics, the nature of the goods exchanged, the manufacturing methods, and the methodological advances enabling us to understand these past contacts.